Vendor-capacity, Perceived-Familiarity, Perceived- Reputation, dan Personal-values sebagai Faktor Pembeda pada Kelompok Konsumen bagi Tercapainya Online Customers’ Trust: Studi pada Pengguna E-commerce di Indonesia - Hadi, Musthofa; Zain, Djumilah; Sudiro, Achmad (Universitas Brawijaya, Indonesia, 2016)
The objectives of this study are (1) To find the determinant variables that discriminateÂ the consumers'group on trusting or not to the online-transactions, among the dependentÂ variables which consist of vendor-capacity, perceived-familiarity, perceived-reputation,Â and personal values. (2) To find the most differrent variable from those determinantÂ variables found, and (3) To Find the effective strategy to overcome the e-trust barriers inÂ Indonesian online-market. The data collected from 85 samples of Indonesians that experiencingÂ the e-commerce transactions. Many questioners were spread by mailed and directlyÂ spreading to meet the quota. The data analysis that used were Discriminant Analysis andÂ Crosstab Analisis. The result of this study show that from four predicting variables, there areonly two variables that determinant the consumers'choise to trust or not to the onlinetransactions;Â vendor-capacity and perceived-familiarity,- which has significant influenceÂ for this case. The consumers'perceived-familiarity was found as the most influencing variablesÂ that could discriminate the trust of the customers to online-transactions. Therefore, theÂ vendors'strategy should be held to educate the customer and maximizing the customers'Â relationship programs, beside continous improvement of the vendors' capacities as well.